REMOVAL OF LEAD AND COPPER USING RED ALGAE GRACILARIA CHANGII AND ITS ACTIVATED CARBON - MOHAMMED, MUBEEN ISAM (2020)
Heavy metals are non-biodegradable elements that have many toxicological effects on human health and are detrimental to the environment. This study focuses on using red algae, Gracilaria changii, in raw and activated carbon form for removal of heavy metals from aqueous solution. This study consists of three phases; (1) to prepare an adsorbent derived from red algae (RAA) and optimise the production using response surface methodology (RSM), (2) to investigate the sorption efficiency of RRA and red algae activated carbon (RAA) in the removal of both Pb (II) and Cu (II) in batch adsorption study using RSMand (3) to investigate the adsorption capacity of RAA for the removal of both Pb (II) and Cu (II) in a fixed bed column study.